Change in Neurocognitive Function in Patients Who Receive CAR-T Cell Therapies: A Steep Hill to Climb - Evlampia Strongyli; Paschalis Evangelidis; Ioanna Sakellari; Maria Gavriilaki; Eleni Gavriilaki (MDPI AG, 2024)
Immunotherapy with chimeric antigen receptor T (CAR-T) cell therapies has brought substantial improvement in clinical outcomes in patients with relapsed/refractory B cell neoplasms. However, complications such as cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) limit the therapeutic efficacy of this treatment approach. ICANS can have a broad range of clinical manifestations, while various scoring systems have been developed for its grading. Cognitive decline is prevalent in CAR-T therapy recipients including impaired attention, difficulty in item naming, and writing, agraphia, and executive dysfunction. In this review, we aim to present the diagnostic methods and tests that have been used for the recognition of cognitive impairment in these patients. Moreover, up-to-date data about the duration of cognitive impairment symptoms after the infusion are presented. More research on the risk factors, pathogenesis, preventive measures, and therapy of neurocognitive impairment is crucial for better outcomes for our patients.